Psychology Well-Being, Post-Traumatic Growth, and Stress Appraisal on COVID-19 Survivors - Widyorini, Endang; Wijaya, Daniswara Agusta (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2024)
The COVID-19 pandemic has certainly brought many psychosocial stressors, however, some previous studies found that some patients who have recovered from COVID-19 show positive growth psychologically. This study aims to investigate the relationship between psychological well-being, post-traumatic growth, and stress appraisal in COVID-19 survivors. Psychological Well-Being Scale 18 items, Post-Traumatic Growth Inventory, and Stress Appraisal Measure were translated into Bahasa Indonesia prior to the data collection. Those three instruments then were completed online by 136 COVID-19 survivors, ages varied between 18 years old to the elderly have confirmed COVID-19 with severe symptoms. Statistical analysis was conducted to test the hypothesis of the current study. Results show that there is no significant difference in PWB, PTG, and SA levels regarding sex, age groups, and educational background respectively. The correlation between PTG and PWB in COVID-19 survivors was found to be positively significant (r=.241;p=.005). Path analysis reveals that Post Traumatic Growth only plays a mediating role in the relationship between the dimensions of Centrality and PWB and Uncontrollable and PWB. Discussion on how different dimensions of stress appraisal affect how post-traumatic growth plays a mediating role towards better well-being among COVID-19 survivors in Indonesia is elaborated further. Keywords: Stress Appraisal; Post-Traumatic Growth; Psychology Well-Being